Optimal Product Design: Implications for Competition and Growth Under Declining Search Frictions - Menzio, Guido (Econometrica, 2023)
As search frictions in the market for a consumer product decline, buyers are able to locate and access more and more sellers. In response, sellers choose to design varieties of the product that are more and more specialized in order to take advantage of the heterogeneity in buyers' preferences. I find conditions on the fundamentals of the market under which the increase in specialization exactly offsets the decline in search frictions. Under these conditions, the extent of competition and the extent of price dispersion remain constant over time even though search frictions are vanishing. Buyer's surplus and seller's profit, however, grow over time at a constant endogenous rate, as the increase in specialization allows sellers to cater better and better to the preferences of individual buyers.